Performance evaluations and calibrations of soil water content/potential sensors for agricultural soils in eastern Colorado - Varble, Jordan L., author; Chávez, José L., advisor; Andales, Allan A., committee member; Butters, Greg L., committee member; Trout, Thomas J., committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: Decagon 5TE; soil moisture sensor; evaluation; Acclima TDT; CS616; Watermark 200